METODE CERAMAH DALAM PENDIDIKAN MADRASAH IBTIDAIYAH: ANALISIS LITERATUR TENTANG IMPLEMENTASI DAN DAMPAKNYA - Apit Dulyapit, Apit Dulyapit; Samih Lestari (Prodi Pendidikan Guru Madrasah Ibtidaiyah STAIN Teungku Dirundeng Meulaboh, 2024)
Abstract The lecture method is one of the approaches widely used in the learning process at Madrasah Ibtidaiyah. This article aims to analyze the implementation and impact of using the lecture method in the context of education at Madrasah Ibtidaiyah. This research employs a literature review approach by examining various relevant sources, including books, articles, and previous studies on the application of the lecture method in Islamic primary schools. The analysis results indicate that the lecture method can improve students' understanding of the material, although there are challenges regarding student engagement and creativity development. Therefore, this study recommends the need for variation in teaching methods to support the effectiveness of learning at Madrasah Ibtidaiyah. Keywords: lecture method, education, Madrasah Ibtidaiyah, implementation, impact, literature review.